Measurement of quasielastic-like neutrino scattering at ∼3.5 GeV on a hydrocarbon target - Ruterbories D. (2019)
MINERvA presents a new analysis of neutrino induced quasielastic-like interactions in a hydrocarbon tracking target. We report a double-differential cross section using the muon transverse and longitudinal momentum. In addition, differential cross sections as a function of the square of the four-momentum transferred and the neutrino energy are calculated using a quasielastic hypothesis. Finally, an analysis of energy deposited near the interaction vertex is presented. These results are compared to modified genie predictions as well as a NuWro prediction. All results use a data set produced by 3.34×1020 protons on target creating a neutrino beam with a peak energy of approximately 3.5 GeV. .